A cassava mosaic disease epidemiologic factors analysis in the Bas-Congo (DR Congo) zone of savannah. case study: â€œSecteur de Bokoâ€ - J.-Roger, Bansimba Mukiese (International Journal of Biological Research, 2015)
This paper aims at evaluating epidemiologic parameters of the African Cassava Viral Mosaic Disease (CMVD) in 25 cassava farmer’s fields of Â«Secteur de BokoÂ» (DR Congo) on the basis of foliar symptoms observation. The results showed that the infection of the local varieties comes mainly from the cuttings whereas that of the improved varieties comes from the flies. The disease incidence varied between 10% and 88.33% with an average of 43.8%. Severity varied between 2.42 and 3.42 with an average of 2.913. The gravity varied between 17.86% and 87.81% while the systemicity varied between 21.42 and 96.66%. The mean number of whiteflies (Bemisia tabaci) by plant (2.068) revealed a preference of the vectors for the improved variety Kindombe which, however, presents a low severity and a less marked gravity. Globally, the CMVD was more severe for the local variety Mpeko with a score of 3.00. A high correlation was found between the gravity and the number of neighbour fields (-0,437*), the density of culture (-0,431*) and also the systemicity of the disease (0,779**). In addition; it appeared that the land topography strongly influences the disease severity (-0,542**).